2013
DOI: 10.1111/dmcn.12201
|View full text |Cite
|
Sign up to set email alerts
|

Classification of intellectual disability using the Wechsler Intelligence Scale for Children: Full Scale IQ or General Abilities Index?

Abstract: Aim We examined the implications of using the Full Scale Intelligence Quotient (FSIQ) versus the General Abilities Index (GAI) for determination of intellectual disability using the Wechsler Intelligence Scales for Children, fourth edition (WISC-IV). Method Children referred for neuropsychological assessment (543 males, 290 females; mean age 10y 5mo, SD 2y 9mo, range 6–16y) were administered the WISC-IV and the Adaptive Behavior Assessment System, Second Edition (ABAS-II). Results GAI and FSIQ were highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…As for the intervention, previous attempts conducted using former versions of the WISC battery led to unsatisfactory results (e.g., Kavale & Forness, ; Watkins, Kush, & Glutting, ; cf. Koriakin et al, ; Lanfranchi, ). Therefore, large‐scale studies, where it is possible to individuate different clusters of children with DD, are needed to clarify this rehabilitation issue further.…”
Section: Discussionmentioning
confidence: 99%
“…As for the intervention, previous attempts conducted using former versions of the WISC battery led to unsatisfactory results (e.g., Kavale & Forness, ; Watkins, Kush, & Glutting, ; cf. Koriakin et al, ; Lanfranchi, ). Therefore, large‐scale studies, where it is possible to individuate different clusters of children with DD, are needed to clarify this rehabilitation issue further.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the most appropriate educational plans may be made so that the student can maximize his or her strengths while receiving accommodations and modifications to minimize weaknesses. Alternatively, one study found that fewer clinically referred school-aged children met criteria for intellectual disability (and, thus, for the services associated with this categorization) when GAI scores were used instead of FSIQ scores (Koriakin et al, 2013). This may have led to more accurate classification of these children, but ultimately a full understanding of their broad scope of abilities and the educational interventions needed to meet their areas of need is most important, and interpretation of the GAI without concomitant interpretation of the FSIQ and CPI is ill-advised to this end.…”
Section: Discussionmentioning
confidence: 99%
“…Judging from the present evidence, the GAI would seem to be more useful than the FSIQ as an index of intellectual abilities when diagnosing SLD with the aid of the WISC-IV. In the case of children with ID, on the other hand, it seems appropriate to rely on the more powerful measure represented by the FSIQ, since similar scores are observed in the four factor indexes (Koriakin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The GAI has the greatest load on the g-factor, so it could be particularly appropriate for diagnosing intellectual disabilities (ID). On the other hand, a study comparing the GAI and FSIQ in a large sample of children found no evidence to justify dismissing the FSIQ in favor of the GAI (Koriakin et al, 2013). It is worth noting, however, that these findings were based more on children with ID than on cases with a specific learning disability (SLD), and focused mainly on their adaptive functioning.…”
Section: Introductionmentioning
confidence: 99%